VD_FINDINFO Jug / 2011 / 182 vom 25. Mai 2011 - VD Tribunal cantonal (2011)
DÉCISION SUR FRAIS, FRAIS D'ASSISTANCE, DÉFENSE D'OFFICE | 135 al. 3 let. a CPP (CH), 135 al. 4 let. a CPP (CH), 426 al. 1 CPP (CH), 429 CPP (CH)